Guest Editor: Raffaella Origa THYROID DISORDERS IN HOMOZYGOUS β-THALASSEMIA: CURRENT KNOWLEDGE, EMERGING ISSUES AND OPEN PROBLEMS - Vincenzo De Sanctis (Mediterranean Journal of Hematology and Infectious Diseases)
Abstract. Changes in thyroid function and thyroid function tests occur in patients with β-thalassemia major (TM). The frequency of hypothyroidism in TM patients ranges from 4% to 29 % in different reports. The wide variation has been attributed to several factors such as patients' genotype, age, ethnic variations, treatment protocols of transfusions and chelation, and varying compliance to treatment. Hypothyroidism is the result of primary gland failure or insufficient thyroid gland stimulation by the hypothalamus or pituitary gland. The main laboratory parameters of thyroid function are the assessments of serum thyroid-stimulating hormone (TSH) and serum free thyroxine (FT4). It is of primary importance to interpret these measurements within the context of the laboratory-specific normative range for each test. An elevated serum TSH level with a normal range of serum FT4 level is consistent with subclinical hypothyroidism. A low serum FT4 level with a low, or inappropriately normal, serum TSH level is consistent with secondary hypothyroidism. Doctors caring for TM patients most commonly encounter subjects with subclinical primary hypothyroidism in the second decade of life. Several aspects remain to be elucidated as the frequency of thyroid cancer and the possible existence of a relationship between thyroid dysfunction on one hand, cardiovascular diseases, components of metabolic syndrome (insulin resistance) and hypercoagulable state on the other hand. Further studies are needed to explain these emerging issues. Following a brief description of thyroid hormone regulation, production and actions, this article is conceptually divided into two parts; the first reports the spectrum of thyroid disease occurring in patients with TM, and the second part focuses on the emerging issues and the open problems in TM patients with thyroid disorders.